EVALUATION OF CIPC SPRAY FOR SPROUT INHIBITION IN POTATOES UNDER TRADITIONAL STORAGE METHODS - Mehta, Ashiv; Singh, Brajesh; Kumar, Dinesh; Ezekiel, R. (Potato Journal, 2013)
Spray application of CIPC @ 40 and 60 ml/tonne of potatoes significantly reduced sprouting, suppressed sprout growth and reduced total storage losses in potatoes up to 90 days under heap (18-32oC, 52-88% RH) and pit (19-27Â°C, 69-92% RH) storage. CIPC treatment did not affect the processing quality of stored potatoes and the chip colour of potatoes was highly acceptable.